Patologiczne kultury organizacyjne jako bariera rozwoju przedsiębiorstw - Miklaszewski, Lech (Pathological Organizational Cultures as a Barrier of Development of Enterprises, 2008)
The paper presents an influence of organizational culture on strategy of organization's development. The author indicates a destructive role of pathological cultures, proposes a typology of pathological cultures and recognizes animators of such cultures. He considers also motives of existing of pathological organizational cultures, especially in the field of strategic management, referring them to strategic methods, results and essence.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 234-245